KAMPONGS AND THE INFORMAL ECONOMY AS A SMART CITY NARRATIVE FROM THE GRASSROOTS - Fathy, Rusydan; Somantri, Gumilar Rusliwa; Warsilah, Henny (Jurnal Masyarakat dan Budaya, 2023)
Information and communication technology has impacted on the transformation and dynamics of cities in the world, represents by Global city and smart city. Conceptually, it is important to generate narratives at the local level into the global discourse. This research uses a sociological perspective to elaborate on the existence of the kampongs and the informal economy as a space for production, contestation, and negotiation of local aspects in the context of a global city and smart city. In this research, kampong is a case study. Theoretically, this research enrich the study of urban sociology to understand space production at the local level as an alternative narrative in the global city and smart city discourse. Specifically and practically, this research offers ideas about the importance of revitalizing the kampongs economy through smart city implementation.